2021
DOI: 10.1101/2021.09.16.460597
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Adiponectin receptor agonist AdipoRon improves skeletal muscle function in aged mice

Abstract: The loss of skeletal muscle function with age, known as sarcopenia, significantly reduces independence and quality of life and can have significant metabolic consequences. Although exercise is effective in treating sarcopenia it is not always a viable option clinically, and currently there are no pharmacological therapeutic interventions for sarcopenia. Here we show that chronic treatment with pan-adiponectin receptor agonist AdipoRon improved muscle function in male mice by a mechanism linked to skeletal musc… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2
2
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 70 publications
0
3
0
Order By: Relevance
“…14 However, its potential beneficial properties on ageing muscle have been scarcely addressed. 15 It is also un-known whether this molecule does effectively prolong life span in normal (wild-type) mice. An effect on longevity has been observed in a mouse model with a severe form of genetic diabetes; hence, the marked alleviation of diabetes provoked by AdipoRon was, in this case, a major confounding factor.…”
Section: Introductionmentioning
confidence: 99%
“…14 However, its potential beneficial properties on ageing muscle have been scarcely addressed. 15 It is also un-known whether this molecule does effectively prolong life span in normal (wild-type) mice. An effect on longevity has been observed in a mouse model with a severe form of genetic diabetes; hence, the marked alleviation of diabetes provoked by AdipoRon was, in this case, a major confounding factor.…”
Section: Introductionmentioning
confidence: 99%
“…Singh et al 19 found that activated APNrs could mitigate dexamethasone-induced muscle atrophy in vivo through the AMPK pathway, thereby simulating PPAR-γ coactivator 1α. Balasubramanian et al 52 observed that APNr activation promoted skeletal muscle repair in aged mice, which was linked to changes in fibre types, especially oxidative fibres. Given that APNr activation could promote osteogenesis and attenuate adipogenesis in AMUSCs, we verified that whether age-induced skeletal muscle dysfunction could be improved via…”
Section: Discussionmentioning
confidence: 99%
“…As CR works to slow aging in all tissues, it has been suggested that CR may work in part through endocrine factors. The role of hormones, including growth hormone, insulin, insulin-like growth factor 1 (IGF-1) and adiponectin, have been explored by numerous groups, but evidence that one of these hormones is responsible for the beneficial effects of CR remains elusive (Balasubramanian et al, 2021; Bonkowski, Rocha, Masternak, Al Regaiey, & Bartke, 2006; Yu et al, 2019). One endocrine factor that could play a role in CR that has not yet been fully explored is fibroblast growth factor 21 (FGF21).…”
Section: Introductionmentioning
confidence: 99%